2016
DOI: 10.1016/j.jhep.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Imagestream detection and characterisation of circulating tumour cells – A liquid biopsy for hepatocellular carcinoma?

Abstract: Characteristics of tumour tissues can be used to predict outcomes for individual patients with cancer, as well as help to choose their best treatment. Biopsy of liver cancers carries risks, however, and is usually avoided. Some cancer cells enter the blood, and although they are very rare, we have developed a method of finding and characterising them in patients with liver cancer, which we hope will provide a low risk means of guiding treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 23 publications
5
97
0
Order By: Relevance
“…As the nuclei of megakaryocytes are big and with strong DAPI staining, they can be easily identified during CTC analysis. A group of large hyperploid cells with no detectable biomarkers (including epithelial and hepatocellular cancer specific markers) have also been reported recently (36). As the authors did not include any mesenchymal markers, they considered all these cells as CTCs with EMT.…”
Section: Discussionmentioning
confidence: 92%
“…As the nuclei of megakaryocytes are big and with strong DAPI staining, they can be easily identified during CTC analysis. A group of large hyperploid cells with no detectable biomarkers (including epithelial and hepatocellular cancer specific markers) have also been reported recently (36). As the authors did not include any mesenchymal markers, they considered all these cells as CTCs with EMT.…”
Section: Discussionmentioning
confidence: 92%
“…The remaining 1258 individuals belonged to the control group that contained healthy volunteers in 15 studies [2426,29,30,32,33,3542] and patients with various hepatic and tumorous diseases in 15 studies. [3,24,2730,32,34–36,3842] The flowchart for inclusion and exclusion of these studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1. Five of these studies came from Europe, [23,24,3335] 13 from Asia, [25,26,2832,36–39,41,42] and the rest from the United States and Egypt. [27,40] Four studies were published before 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found a strong association between CTC counts and the karyoplasmic ratio, presence of microvascular invasion (MVI), and HCC prognosis. With technological advancements, multimarker combinations, including pERK and pAkt [48], EMT markers (twist and vimentin) [49], MAGE-3 and survivin [50], CK, EpCAM and Glypican-3 [51], Annexin V, EpCAM, ASGPR1 and taMPs [52], were used in CTC detection for evaluating metastasis and prognosis and for monitoring the efficacy of sorafenib. In addition to the various detection methods mentioned above, the CTC-Chip has been considered an effective microfluidic device for capturing these EpCAM-expressing cells based on antibody-coated microposts [5356].…”
Section: Introductionmentioning
confidence: 99%